Sophisticated Methods for Tissue Perfusion Evaluated - Libor Hargas; Dusan Koniar; Stanislav Stofan; Miroslav Hrianka (Communications - Scientific letters of the University of Zilina, 2011)
This paper focuses on image acquisition system designing for biomedical image enhancement. It introduces the possibilities of diagnostics and analysis of tissue via virtual instrumentation. The two dimensional images shot by the camera provide information about the surface properties and degradation of a real skin. The main idea is based on the human skin parameters measured for healthy and ill skin. The aforementioned access provides parameters evaluation by creating a structure model. The anomalies are recognized by this model.